Investigating Academic Dishonesty among Undergraduate Students: Do Gender and Majors Matter? - Damajanti Kusuma Dewi; Desi Nurwidawati; Amjodti Laili Agindaris; Irena Yolanita Maureen (IJORER : International Journal of Recent Educational Research, 2025)
Objective: The research aims to understand the extent of academic dishonesty among students in a faculty at a university in a developing country, defining the various types of dishonesty and pinpointing the factors that trigger such behavior; to formulate a profile of academic dishonesty as a guideline for the level of academic dishonesty in the faculty. The research involved subjects from eight departments, which had never been carried out by other researchers before. Method: Data were collected via a survey using a Google Form, employing the Academic Dishonesty instrument and tailored to the Indonesian context. This instrument, which consists of 23 items, covers six factors: cheating in examinations, plagiarism, outside help, prior cheating, falsification, and lying in academic assignments. Results: First, there is a significant difference in academic dishonesty scores between male and female groups, with a significance value of 0.019 (p < 0.05). Second, there is no significant difference in academic dishonesty scores based on majors between male and female groups, as indicated by the significance value of 0.060 (p > 0.05). The final conclusion is that there is no significant difference in academic dishonesty scores based on the interaction between gender and majors within each population group, as evidenced by the significance value of 0.331 (p > 0.05). This study contributes to filling a critical gap in the literature and offers valuable insights for developing targeted interventions across diverse educational contexts.